Conductas problemas infantiles: Indicadores evolutivos y emocionales en el dibujo de la figura humana - Barros, Maria Cecilia; Ison, Mirta Susana (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Human Figure Drawing test (HFD) was been used to compare drawings of children with and without behavioral disorders. This. was been undertaken to: (1) evaluate differences in intellectual maturity level between both groups, and (2) to compare emotional indicators in children's drawings. A total of 284 HFD were evaluated considering a diversity of indicators. Results concerning intellectual maturity showed that boys with behavioral disorders scored lower than boys without behavioral disorders. As regards emotional indicators, we found noticeable differences with Koppitz' (1989) findings. In this sample, signs that arc supposed to be unusual were observed more frequently and fewer differences than expected were found between boys with and without behavioral disorders.